Cortical activation patterns in healthy subjects during the traditional Japanese word generation task Shiritori determined by multichannel near-infrared spectroscopy. Issue 1 (December 2016) - Nakahachi, Takayuki; Ishii, Ryouhei; Canuet, Leonides; Takahashi, Hidetoshi; Ishitobi, Makoto; Kamio, Yoko; Iwase, Masao
Abstract Background Shiritori is a traditional Japanese game based on word generation to letters (WGL). This game is familiar to most Japanese people, young and old. Previous functional neuroimaging studies using magnetoencephalography and functional magnetic resonance imaging suggested that compared to conventional WGL, Shiritori could activate broader cortical areas, including the frontal lobe and the superior temporal cortex in healthy subjects. These studies were conducted under restricted experimental conditions without overt speech, that prevented the subjects from performing naturally theShiritori task. The present study aims to determine cortical activation patterns in healthy subjects during theShiritori task with overt speech. Methods Twenty-five healthy Japanese native speakers were investigated using multichannel near-infrared spectroscopy, which is not sensitive to motion artifact caused by overt speech and is able to cover frontal and superior temporal areas. Results Significant hemodynamic responses were widely distributed over the frontal and superior temporal cortex bilaterally. The activity could be divided into four clusters, with the channels in each cluster showing similar hemodynamic responses, one of which appears to correspond to the frontal and temporal language-related networks in the brain. Conclusions Cognitive functions subserved by fronto-temporal regions are elicited byShiritori task with overt speech in healthy subjects. Thus, Shiritori might potentially be used as a clinically-relevant task to activate language-related networks in the brain.